Perspektivy stilistiki diskursa v svete dalʹnej i otložennoj pragmatiki - Hazagerov, Georgij G. (Stylistyka, 2020)
This páper reports on the dynamics of the anthropocentrism principle which has deter- mined three development stages o f linguistic pragmatics - communicative, cognitive and discursive ones. In the first (communicative) slage the anthropocentrism principle in the pragmatics involves emphasis on speech acts of one communicant. The second (cognitive) stage is characterized by applying to mental States o f the communicant and aims to explain the relationship language - mind ~ speec h , on the one hand, and involvement of interdisciplinary relations, on the other hand. In the third (discursive) stage, the anthropocentrism principle expands to cognitive and speech interaction o f communicants and their groups within discourses of different types signifying the leading role o f linguistic pragmatics in the evolvemenl o f discourse linguistics. An overview of discourse interpretations is given which include: research materiał (discourse is a text, an excerpt of a text or a complex of texts), object (discourse is a process) and subject (discourse is a unity o f communication process and text).